Clinical evaluation of domestic dental whitening strategies (Research, Society and Development, 2021)
Tooth bleaching has become the first clinical option in reversing chromatic changes. This study evaluated the efficiency of four different approaches for home-based chemically induced tooth whitening. 32 patients were randomly distributed into four groups (n=8), according to the bleaching technique performed: G1: control group – at-home dental bleaching with 10% carbamide peroxide (Whiteness Perfect/FGM) delivered in a customized tray, G2: teeth whitening pen containing hydrogen peroxide (Walgreens), G3: night-time whitening gel (CVS) containing hydrogen peroxide and G4: whitening strips (3D White Oral B) containing 10% hydrogen peroxide. Chromatic changes (ΔE) were collected at baseline and at the middle and end of the treatment, using a digital spectrophotometer (EasyShade – Vita). Tooth sensitivity, gingival irritation, and degree of satisfaction were also recorded. The comparison between the average ΔE means, considering the final and initial values, revealed a statistically significant difference between the results obtained by G1 (ΔE2=11.65) and the other groups (ΔE2 of G2=4.38, G3=4.83 and G4 = 8.32). No significant difference was observed in the occurrence of tooth sensitivity and gingival irritation. The patients from G1 and G4 were more satisfied with the treatment outcome.